Formulation and Evaluation of Valsartan Tablets Using Starch Succinate as Novel Super Disintegrant by Using 32 Factorial Design - Lakshmi, Kollipara Naga Venkata Chenchu; Aminabee, Shaik; Shankar, Kunderu Ravi; Ramana, Gangireddy; Sultana, Shaik Almaas; Keerthana, Dasari Naga Rama; Sri, Gundu Bhagya; Niharika, Challa Suma (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim The current study focuses on enhancing the dissolution pace of Valsartan, as BCS Class II. The objective is to develop fast-dissolving tablets of Valsartan by forming complexes with β-Cyclodextrin (β-CD). Materials and Methods To achieve this, Valsartan-βCD (1:1 M) complexes were prepared and used to formulate tablets with the help of primojel and starch succinate, following a 32 design approach. Results The tablet powder blends demonstrated excellent flow properties, making them suitable for direct compression. All the prepared tablets met the disintegration time specifications outlined in the Indian Pharmacopoeia for uncoated tablets. The design of the Valsartan fast-dissolving tablet formulation was based on 3 levels of factor X1 (Primojel) at concentrations of 5%, 6.25% and 7.5%, and 3 levels of factor X2 (starch succinate) at concentrations of 5%, 6.25%, and 7.5%, with respect to the mean weight of the tablet (250 mg).The study further established equations for Disintegration Time (DT) and the Portion of Drug dissolved in 10 min (PD10) to evaluate the performance of the formulated fast-dissolving Valsartan tablets. Based on the obtained results, it is evident that intensifying the amount of the super disintegrants in the formulation ensued in a decrease in the disintegration time of the dosage form. Conclusion The optimized tablet (C1) demonstrated promising attributes with a disintegration time of only 15 sec and an impressive 85.69% dissolution within 10 min. Consequently, the successful formulation of fast-dissolving tablets of Valsartan was achieved through the use of primojel and starch succinate, a novel super disintegrant.
Keywords: Valsartan; Starch Succinate; Fast Dissolving Tablets; Primojel; Optimization